Percepção ambiental : a construção de caminhos para a sustentabilidade no Instituto Federal de Educação, Ciência e Tecnologia de Sergipe (IFS) - Costa, José Sérgio Filgueiras (2021)
The interactive process of man with the environment has always been linked to the perception of each individual, which can be influenced by factors such as: communication, education, culture and socioeconomic status. Studying the theme of perception and practices of environmental sustainability is essential to fundamentalize and proportionate actions to sensitize society about the importance of the correct use of natural resources and conservation of the environment. For this reason, this research sought to make a diagnosis of the environmental perception of the publics of the Federal Institute of Education, Science and Technology of Sergipe (IFS): teachers, students and administrative technicians in education. Having knowledge of the connection profile of this community with the environment is essential to direct actions of education and awareness of environmental sustainability. For a promising environmental education process, it is vital that communication is compressive and that environmental education has an interdisciplinary character. The National Education Policy (PNE) mentions that environmental education must be treated at all levels of education, in formal and informal contexts. For that, it became necessary a bibliographic research about the themes "environmental education", "environmental sustainability", "environmental perception" and "organizational communication". The research was descriptive and exploratory, with a predominantly qualitative approach. Data collection was carried out by means of a semistructured questionnaire applied with servers and students, through the Google Platform online form. Analysis of the results made using the Bardin methodology, which works with content analysis. The investigation pointed to a negative environmental perception of the researched public with regard to the global, national, regional and institutional contexts. This highlights the need to increase interdisciplinary environmental education actions. Such educational actions may include, in particular, knowledge about the factors that generate solid waste and the destination given to garbage, as well as critical reflections, with the purpose of broadening the discussion to the social, environmental, economic, political and cultural contexts. It is concluded that the studies of perception, environmental sustainability and organizational communication are essential to improve Environmental Education carried out in several areas of teaching and learning.